2020
DOI: 10.1186/s12936-020-03245-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of reactive case detection for malaria elimination in southern Zambia: a cross-sectional study

Abstract: Background: Reactive case detection (RCD) seeks to enhance malaria surveillance and control by identifying and treating parasitaemic individuals residing near index cases. In Zambia, this strategy starts with passive detection of symptomatic incident malaria cases at local health facilities or by community health workers, with subsequent home visits to screen-and-treat residents in the index case and neighbouring (secondary) households within a 140-m radius using rapid diagnostic tests (RDTs). However, a small… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 44 publications
0
24
2
Order By: Relevance
“…In this study, malaria prevalence was 31.6 % for Sussundenga Village, higher than the prevalence recorded in Chimoio city [16] of 20.1 % In the neighboring Zimbabwe, malaria prevalence was 19.5 % in Mutare and 50.9 % in Mutasa districts in 2016. [17] and in Zambia a study reported parasite prevalence between 0.7 and 1.8 % [18]. And 34 % in…”
Section: Discussionmentioning
confidence: 96%
“…In this study, malaria prevalence was 31.6 % for Sussundenga Village, higher than the prevalence recorded in Chimoio city [16] of 20.1 % In the neighboring Zimbabwe, malaria prevalence was 19.5 % in Mutare and 50.9 % in Mutasa districts in 2016. [17] and in Zambia a study reported parasite prevalence between 0.7 and 1.8 % [18]. And 34 % in…”
Section: Discussionmentioning
confidence: 96%
“…Many of these findings are consistent with prior findings using epidemiologic and genetic data to identify focal transmission and can inform the National Malaria Elimination Programme on how to efficiently deploy interventions to interrupt transmission and achieve malaria elimination. 9 , 10 , 12 , 21 , 22 , 38 Many previous studies have focused on the spatial extent and methods for screening and timing of potential follow-up visits in programs. 21 , 23 , 39 , 40 Reactive screen-and-treat is now being implemented across several sub-Saharan African countries using similar methods as in southern Zambia.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 12 , 21 , 22 , 38 Many previous studies have focused on the spatial extent and methods for screening and timing of potential follow-up visits in programs. 21 , 23 , 39 , 40 Reactive screen-and-treat is now being implemented across several sub-Saharan African countries using similar methods as in southern Zambia. 9 , 11 , 16 These have led to improved surveillance and an identification of an increased number of parasitemic individuals but have yet to successfully reduce transmission or achieve elimination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations